Chromosome-Level Haplotype Assembly for Equus asinu - Miao, Xinyao; Yu, Yonghan; Zhao, Zicheng; Wang, Yinan; Qian, Xiaobo; Wang, Yonghui; Li, Shengbin; Wang, Changfa (Frontiers in Genetics, 2022)
ABSTRACT: >Background Haplotype provides significant insights into understanding genomes at both individual and population levels. However, research on many non-model organisms is still based on independent genetic variations due to the lack of haplotype. >Results We conducted haplotype assembling for Equus asinu, a non-model organism that plays a vital role in human civilization. We described the hybrid single individual assembled haplotype of the Dezhou donkey based on the high depth sequencing data from single-molecule real-time sequencing (30×), Illumina short-read sequencing (211×), and high-throughput chromosome conformation capture (56×). We assembled a near-complete haplotype for the high-depth sequenced Dezhou donkey individual and a phased cohort for the re-sequencing data of the donkey population. >Conclusions Here, we described the complete chromosome-scale haplotype of the Dezhou donkey with more than a 99.7% phase rate. We further phased a cohort of 156 donkeys to form a donkey haplotype dataset with more than 39 million genetic variations.